PENGARUH LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI : (Studi pada Pemerintah Kabupaten Kepulauan Selayar) - Sri Ulfa Ferliani; Firda Hidayati; Niken Lastiti (Jurnal Administrasi Publik, 2022)
: The success of an organization is certainly influenced by the performance of its human resources or employees. Problems related to the work environment such as inadequate facilities and infrastructure or work facilities are one of the problems that occur in Selayar Islands Regency as the only Archipelago Regency in South Sulawesi Province. This study aims to determine and analyze the effect of the work environment on employee performance in Selayar Islands Regency. The method used is quantitative with descriptive and inferential analysis techniques. The hypothesis test uses Structural Equation Modeling (SEM) with the Partial Least Square (PLS SEM) analysis method through Smart PLS 3.0. The sample used was 176 respondents who came from 4 regional apparatus organizations in the Selayar Islands Regency which performed less well. The results of the study show that there is a positive and significant influence between the work environment on employee performance. This means that the better the work environment, the employee's performance will increase. Based on these results, it is hoped that the Selayar Islands Regency government can improve its performance.